Evaluation of Dietary Fishmeal Analogue with Addition of Shrimp Soluble Extract on Growth and Nonspecific Immune Response of Rainbow Trout, Oncorhynchus mykiss. Issue 4 (9th September 2016) - Jo, Hayun; Lee, Seunghan; Yun, Hyeonho; Hong, Jeongwhui; Moniruzzaman, Mohammad; Bai, Sungchul C.; Park, Gunhyun; Chee, Seokwoo; Jeon, Tae‐Eun
Abstract: A 12‐wk feeding trial was conducted to evaluate the effects of the dietary fishmeal analogue (FMA) adding 2% shrimp soluble extract (SSE) on growing rainbow trout, Oncorhynchus mykiss . Fish averaging 146 ± 3.8 g (mean ± SD) were randomly distributed into 500‐L aquaria as groups of 20 fish per tank. Fish were fed the experimental diets in triplicate groups to apparent satiation twice a day on a dry matter basis. Each group was fed one of the four experimental diets: control (FM100% + FMA0%), FMA0 (FM100% + FMA0% + SSE2%), FMA12 (FM88% + FMA12% + SSE2%), and FMA24 (FM76% + FMA24% + SSE2%). After the feeding trial, weight gain and specific growth rate of fish fed the FMA0 and FMA12 diets were significantly higher than those of fish fed the FMA24 diet ( P < 0.05). Feed efficiency and protein efficiency ratio values of fish fed the control, FMA0, and FMA12 diets were significantly higher than those of fish fed the FMA24 diet ( P < 0.05). The values of superoxide dismutase activity showed significantly higher amounts for the FMA0, FMA12, and FMA24 groups than the control group ( P < 0.05). Lysozyme activity in the FMA12 group was significantly higher than in the control group ( P < 0.05). Therefore, according to our results, FMA with additive SSE can be used up to 12% as a substitute of fishmeal for growing rainbow trout.